Left ventricular outflow tract obstruction after transcatheter mitral valve replacement: a case report with a multifaceted approach - Caneiro-Queija, Berenice; Guerreiro, Claudio E.; Echarte-Morales, Julio; Estévez-Loureiro, Rodrigo; Barreiro-Pérez, Manuel; González-Ferreiro, Rocío; Estévez-Cid, Francisco; Legarra, Juan José; Baz, Jose Antonio; Íñiguez-Romo, Andrés (Frontiers in Cardiovascular Medicine, 2024)
An 83-year-old woman was admitted to our center because of heart failure. Transthoracic echocardiography revealed severe mitral annular calcification resulting in a double mitral valve lesion. After discussion by the heart team, transcatheter mitral valve replacement with Tendyne (Abbott Structural, Santa Clara, CA, USA) was performed. Despite having a predicted neo-left ventricular outflow tract (LVOT) above the cut-off value, the patient developed clinically significant LVOT obstruction (LVOTO) refractory to medical treatment. This situation is often treated before the intervention, and dealing with LVOTO afterward can be challenging. After taking the patient's anatomy into consideration, we decided to perform alcohol septal ablation. Applying a combined strategy of medical treatment and intervention led to success. In this case report, we discuss this event and the strategies available for preventing and managing the condition.